Toxic Epidermal Necrolysis Associated with Antiepileptic Drugs and Cranial Radiation Therapy - Shereen Elazzazy; Taghrid Abu Hassan; Ashraf El Seid; Cicy Mary Jacob (Case Reports in Oncological Medicine)
Case reports on the development of toxic epidermal necrolysis (TEN) associated with concurrent administration of phenytoin with cranial radiation therapy (Ahmed (2004), Criton et al. (1997), and Rzany et al. (1996)), but reports about erythema multiforme, which can develop in patients treated with levetiracetam and cranial irradiation, are very limited. This paper presents evidence that TEN may be induced by concurrent use of radiation with both phenytoin and levetiracetam. Our case is a 42-year-old male patient, a case of gliosarcoma who developed purpuric dermatitis associated with phenytoin when combined with cranial radiation therapy; although phenytoin was discontinued and switched to levetiracetam, the patient had more severe symptoms of toxic epidermal necrolysis (TEN) on levetiracetam; the patient improved with aggressive symptom management, discontinuation of antiepileptic drugs (AEDs), and holding radiotherapy. Although TEN is a rare toxicity, physicians should pay a special attention to the monitoring of brain tumor patients on antiepileptic prophylaxis during cranial irradiation; furthermore, patients should be counselled to notify their physicians if they develop any new or unusual symptoms.